INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN BANGUN GEOMETRI MELALUI MODEL PEMBELAJARAN KONTEKSTUAL DI SEKOLAH DASAR - Mandasari, Nur Kibah; Apriyanda, Apriyanda; Zahratunisa, Ilda; Nasution, Suhailah Haya; Syahrial, Syahrial; Saragih, Doni Irawan (Jurnal Merah Putih Sekolah Dasar, 2025)
This study was conducted in response to the limited number of studies examining the integration of local wisdom in geometry learning at the elementary school level, despite its potential to enhance conceptual understanding and cultural preservation. The purpose of this study is to analyze the integration of local wisdom in teaching geometric shapes through a contextual learning model in elementary schools. This research employed a qualitative approach using a library research method. Data were collected from relevant national and international literature and analyzed through thematic synthesis to identify patterns, concepts, and effective instructional strategies. The findings indicate that elements of local culture, such as traditional buildings, fabric motifs, traditional games, arts, and community traditions, contain various geometric concepts that can be utilized as contextual learning resources. The application of Contextual Teaching and Learning (CTL) integrated with local wisdom has been shown to improve students’ motivation, conceptual understanding, and engagement by connecting abstract geometric concepts with students’ real-life experiences. Furthermore, this approach contributes to strengthening students’ cultural awareness and appreciation. The study concludes that integrating local wisdom into geometry learning through a contextual model enhances instructional effectiveness while supporting the development of ethnomathematics-based learning and cultural preservation in elementary education.